How to use the compound microscope (California : Clearvue/eav, 1998)
Contains many features: Presentation, encyclopedia, dictionary, word search, question, quizzes, glosarry and indexes
System requirements: Windows 486DX/66 MHz processor, Windows 3.1, Windows 95 or later, 8 MB RAM (16 MB RAM recommended for Windows 95), CD-ROM drive, 640 X 480 SVGA (minimum 256 colors), 3 MB hard disk space required for QuickTime
Keywords: Microscopy -- Technique; Microscopes -- Technique